Dynamic patterns of electroosmosis peristaltic activity of a Jeffery fluid with double diffusion and hall effect through a tapered rotational microfluidic system - S. Ravikumar; S. Farooq; Manish Gupta; Mohamed M. El-Toony; Eman A. Ayob (Results in Engineering)
This article discusses the computational analysis of the electroosmosis peristaltic activity of a non-Newtonian fluid with Joule heating and diffusion effects in a tapered wavy conduit. The peristaltic wave approach constructs the current model's framework with nonuniform boundaries that exhibit distinct amplitudes and phases. Lubrication theory (assuming a long wavelength) and the low Reynolds number approximation (Stokes flow) have been used to obtain an appropriate solution. Furthermore, the Poisson-Boltzmann equations are simplified using the Debye-Hückel linearization. A comparison will be made with previously published results in the available literature to assess the reliability and accuracy of the current findings. The electroosmotic parameter and the helmholtz-smoluchowski velocity significantly enhanced fluid velocity. This phenomenon is essential in biological applications such as drug administration, lab-on-chip technologies, and fluid transport management inside microfluidic devices, enabling accurate fluid manipulation at the micro or nanoscale. An elevating the soret and dufour numbers amplifies the interaction between energy and mass transmission, resulting in an increase in the fluid temperature. This may facilitate regulated mixing, enhance thermal management in organ-on-chip systems, or accelerate biological processes. The need for optimum design in sensitive applications is emphasized by the imperative to meticulously control biomolecules and cells to avert harm from excessive heating. Moreover, an increase in the joule heating parameter results in a decrease in fluid concentration due to enhanced thermal effects. Joule heating plays a crucial role in therapeutic applications, including electrotherapy and cancer treatment through hyperthermia, as it improves the effectiveness of chemotherapy and radiation by selectively heating targeted tissues. The skin friction coefficient increases in the channel's center due to the influence of the electroosmotic parameter. The Jeffery fluid parameter shows an increasing trend in pressure rise for both peristaltic and retrograde pumping sectors.